2016
DOI: 10.1177/2150135116659651
|View full text |Cite
|
Sign up to set email alerts
|

Absent Pulmonary Valve Syndrome With Tricuspid Atresia, Ventricular Septal Defect, and Aneurysmal Dilated Pulmonary Artery: A Case Report of Successful Fontan Completion

Abstract: Of the associated cardiac defects with absent pulmonary valve, the combination of tricuspid atresia, ventricular septal defect, and aneurysmal dilatation of the pulmonary arteries is very rare. We report the case of a low-birth-weight girl (2,282 g) with this anomaly, which was prenatally diagnosed. Fontan completion was successfully achieved at 16 months of age, following staged palliative procedures including banding of the main pulmonary trunk and plication of the aneurysmal dilated central pulmonary artery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“… 2 A case report in 2018 described a patient with prenatally diagnosed APVS along with tricuspid atresia, a VSD, and dilated pulmonary arteries, initially palliated with main pulmonary artery banding and plication of the aneurysmal dilated central pulmonary artery and later completed with a Fontan procedure at 16 months of age. 5 Surgical options include single-ventricle palliation, but heart transplantation should always be a consideration. In a 2014 retrospective review by Szwast et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 A case report in 2018 described a patient with prenatally diagnosed APVS along with tricuspid atresia, a VSD, and dilated pulmonary arteries, initially palliated with main pulmonary artery banding and plication of the aneurysmal dilated central pulmonary artery and later completed with a Fontan procedure at 16 months of age. 5 Surgical options include single-ventricle palliation, but heart transplantation should always be a consideration. In a 2014 retrospective review by Szwast et al.…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 retrospective single-center study reported an incidence of 8% ( n = 1) for APVS with tricuspid atresia, right ventricular dysplasia, and a restricted duct 2 . A case report in 2018 described a patient with prenatally diagnosed APVS along with tricuspid atresia, a VSD, and dilated pulmonary arteries, initially palliated with main pulmonary artery banding and plication of the aneurysmal dilated central pulmonary artery and later completed with a Fontan procedure at 16 months of age 5 . Surgical options include single-ventricle palliation, but heart transplantation should always be a consideration.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,13,15 Only a handful of cases successfully palliated to the stage of Fontan have been described in the literature. 11,12,[16][17][18][19] Several aspects of TA.APV make it a unique challenge to manage (Figure 4). The ultimate goal of surgical intervention is the construction of an efficient Fontan circuit through three stages as for any other form of the single ventricle.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Successful palliation to second stage has been described occasionally 10,11,13,15 . Only a handful of cases successfully palliated to the stage of Fontan have been described in the literature 11,12,16–19 . Several aspects of TA.APV make it a unique challenge to manage (Figure 4).…”
Section: Commentmentioning
confidence: 99%
“…In this paper, we wanted to remember other cardiac anomalies associated with absent pulmonary valve syndrome with tetralogy of Fallot. Çeşitli çalışmalar yapılmış ve PKYS'ye eşlik edebilecek anomaliler yayınlanmıştır: Sol pulmoner arter yokluğu, sol pulmoner arterin PDA'dan çıkması, sağ pulmoner arterin asendan aortadan çıkması ve sağ arkus aorta, triküspit atrezisi, sol pulmoner arterin asendan aortadan çıkması, sol ana koroner arter atrezisi, aort koarktasyonu, Ebstein anomalisi, dekstrokardi, atriyoventriküler septal defekt, büyük arterlerin transpozisyonu, trikuspit atrezisi veya ağır triküspit stenozu, intakt ventrikular septum, kesintili aortik ark tip B, aortopulmoner kollateraller, double aortik ark ile birliktelik bildirilmiştir (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Olguunclassified